Spillover effects of foreign currency loans: The role of the bank lending channel - Palma Filep-Mosberger; Lorant Kaszab; Zhou Ren (Magyar Nemzeti Bank, 2024)
Local currency borrowers are statistically significantly affected by exchange rate fluctuations due to the bank lending channel. Using microdata on borrowers from Hungary, this study examines the spillover effects of foreign currency loans on local currency borrowers following an unexpected appreciation of the Swiss franc (CHF) in January 2015. CHF corporate loans are considered unhedged since the majority of the borrowers did not have income in CHF. Our analysis indicates that banks holding a larger portion of unhedged CHF corporate loans reduced their lending in local currency corporate loans after the shock. This relationship is robust across both extensive (loans terminated by a given bank and no new loans at a bank or banks different from the account holder bank or banks) and intensive (no new loans at its current bank or banks) margins. Further investigation into the mechanisms reveals that banks with more unhedged CHF corporate loans experience an increase in non-performing CHF loans post-shock, reducing their capital adequacy. Furthermore, the evidence in our paper suggests that reductions in banks' local currency lending due to exchange rate shocks adversely affect the investment activity of small firms and increase their likelihood of default.
Keywords: G15; G21; G28; G32; G33; 330; bank lending; exchange rate shock; currency mismatch; FX loans; credit